Age-constraints on fabric reactivation in the Tusas Range, northern New Mexico, using electron-microprobe monazite geochronology; implications for the nature of regional approximately 1400 Ga deformation - Joseph P Kopera; Williams, Michael L.; Jercinovic, Michael J. (Abstracts with Programs - Geological Society of America, 2002)
A key issue in constructing models for the southward growth of Laurentia during the Proterozoic is distinguishing the effects of approximately 1650 Ma and approximately 1400 Ma tectonism. These events share similar styles of deformation and metamorphism, making it difficult to assign structures, fabrics, and metamorphic phases to a particular event. The fundamental geometry of this orogen in the southwestern United States is defined in many areas by fold-fault pairs and isolated synclines of thick approximately 1700 Ma quartzite. In-situ EMP chemical dating of monazite, combined with detailed structural analysis, indicates that such synclines within the Tusas Range of northern New Mexico (locally F (sub 3) ) were substantially modified, if not developed, during approximately 1400 Ma tectonism. Monazite grains from the Ortega quartzite in the central Tusas Range display a shape preferred orientation parallel to the axial-planar fabric of these folds (S (sub 3) ), with overgrowth rims preferentially developed in the X direction of strain. These monazite grains have either >1700 Ma cores or approximately 1650 Ma cores with approximately 1400 Ma overgrowth rims, or are entirely approximately 1400 Ma in age. Field and microstructural observations show that the upright, east-west trending F (sub 3) and S (sub 3) are reactivations of older, northwest-trending fabrics and structures. The presence of approximately 1650 Ma overgrowth rims on monazite grains from the central and northern Tusas Range implies that these folds and fabrics may have nucleated prior to approximately 1400 Ma tectonism. Previous studies have shown an increase in approximately 1400 Ma monazite ages from north to south within the range, consistent with a similar increase in metamorphic grade. This gradient suggests that the central and northern Tusas may have been at progressively shallower crustal levels during approximately 1400 Ma tectonism, thus increasing the preservation of older fabrics, structures, and metamorphic monazite from south to north within the range. These observations support the hypothesis that approximately 1400 Ma tectonism locally reactivated and utilized pre-existing structures and fabrics, but had also profoundly shaped the geometry and metamorphic character of the orogen.
Keywords: #StaffPubs; dates; deformation; electron probe data; fabric; folds; geochronology; Geochronology 03; geometry; in situ; Laurentia; Mesoproterozoic; metamorphism; monazite; New Mexico; northern New Mexico; orogeny; Ortega Group; overgrowths; phosphates; Precambrian; preferred orientation; proterozoic; reactivation; Southwestern U.S.; strain; structural analysis; Structural geology 16; synclines; tectonics; Tusas Mountains; United States; upper Precambrian; zoning

Arsenic in central Massachusetts bedrock and groundwater - McTigue, David F.; Stein, Carol L.; Brandon, William C.; Joseph P Kopera; Keskula, Anna J.; Koteas, G. Christopher (Abstracts with Programs - Geological Society of America, 2010)
Across the New England "arsenic belt," groundwater arsenic (As) concentrations often exceed the EPA's 0.01-mg/L drinking water standard. In overburden groundwater at a site within this belt in north-central Massachusetts, As has been reported at levels up to 7.6 mg/L. Bedrock at the site consists of Silurian Central Maine Terrane metasediments intruded by the Devonian Ayer granodiorite and Chelmsford granite. Exchange of hydrothermal fluids between these lithologies during intrusion and later deformation, faulting, and metamorphism resulted in crystallization of arsenic-bearing minerals, including arsenopyrite. Quaternary deglaciation and unloading dilated joint systems in the bedrock, allowing increased exposure of the mineralogy to meteoric water. Several arsenopyrite alteration products (e.g., scorodite), of varying solubilities, precipitated on fracture surfaces and along grain boundaries between major phases. In the emerging conceptual model for this site, groundwater is recharged in bedrock uplands and moves downgradient through the fracture network, becoming increasingly reducing as it moves along a flow path. Arsenic dissolved from arsenopyrite and arsenic-bearing alteration phases in bedrock remains in solution until the groundwater discharges to lowland areas hydraulically downgradient. In these adjacent lowlands, glacial sand and gravel overburden lies above the bedrock. When the reducing water reaches more oxidizing conditions, As-sorbing hydrous ferric oxides (HFO) precipitate out on the aquifer solids, resulting in accumulation of As in the deep overburden aquifer. A large landfill at this site, now closed and capped, imposed reducing conditions, and As is mobilized into groundwater by reductive dissolution of the HFO. The presence of elevated As in groundwater is consistent with arsenic-bearing phases generated in granitoids at depth during regional metamorphism, which were subsequently altered, and are being solubilized at present by the circulation of shallow groundwater through varying redox environments. This scenario is supported by geochemical and petrographic studies of the granitoids and the occurrence of the highest groundwater and soil arsenic concentrations in the adjacent deep overburden.
Keywords: #StaffPubs; alteration; arsenic; arsenides; arsenopyrite; Ayer Granodiorite; BEDROCK; central Massachusetts; chelmsford granite; Devonian; dilation; discharge; dissolved materials; drinking water; Eh; fractures; General geochemistry 02A; geochemistry; granites; ground water; igneous rocks; joints; massachusetts; metals; metamorphism; meteoric water; overburden; Paleozoic; petrography; plutonic rocks; pollutants; reduction; solubility; solution; sulfides; theoretical models; United States

Evidence for arsenic-mineralization in granitic basement rocks, Ayer Granodiorite, northeastern Massachusetts - Koteas, G. Christopher; Keskula, Anna J.; Stein, Carol L.; McTigue, David F.; Joseph P Kopera; Brandon, William C. (Abstracts with Programs - Geological Society of America, 2010)
Core samples of the Ayer Granodiorite along the eastern margin of the Merrimack Belt in northeastern Massachusetts host a series of sulfide and oxide phases that resulted from interaction with sulfide-bearing meta-sedimentary host rocks. Euhedral arsenopyrite grains are found with ilmenite, apatite, and REE phosphates in zones that generally mimic the intersection between a gneissic fabric and a relict magmatic foliation. Arsenopyrite crystals are typically elongate with this lineation. Euhedral to subhedral pyrite crystals have also been observed, but are localized to areas without As-bearing phases. Micro-fractures that parallel either a steep NW-striking joint set or gently-dipping sheeting joints are commonly filled with interwoven calcite cements and As-bearing Fe-oxides. Surface coatings of major fracture sets are also characterized by Fe-As-rich rinds that host micron-scale sub-angular particles of quartz, feldspars, and phyllosilicates. Where micro-fractures are most concentrated, sulfide-bearing minerals are less common; however, subhedral to anhedral arsenopyrite grains do occur along some open micro-fractures. These crystals preserve lobate grain boundaries and are associated with As-bearing Fe-oxide-rich coatings along adjacent fractures. The presence of 1) pyrite, 2) arsenopyrite associated with phosphates, and 3) As-bearing fracture coatings suggests multiple stages of mineralization. We propose that intrusion-related fluid-rock interaction associated with heating of nearby sulfide-bearing schists of the Berwick Formation during Acadian orogenesis may have provided the necessary constituents for growth of sulfide phases in the Ayer. It appears that Late Devonian greenschist facies metamorphism and metasomatism led to mineralization that generated arsenopyrite and accompanying phosphates; however, the role of the cross-cutting Clinton Newbury Fault Zone as a conduit for hydrothermal fluids may also be important. Lower temperature As-bearing Fe-oxide and calcite coatings on open fractures surfaces may be associated with a change from lithostatic- to hydrostatic-pressures during post-glacial regional uplift. This mineralization appears to be synchronous with intense microfracturing that post-dates all other mineralization.
Keywords: #StaffPubs; acadian; arsenic; arsenides; arsenopyrite; Ayer Granodiorite; Berwick formation; fractured materials; geochemistry; granodiorites; Igneous and metamorphic petrology 05A; igneous rocks; lower Paleozoic; massachusetts; Merrimack Synclinorium; metals; metamorphic rocks; metamorphism; metasedimentary rocks; metasomatism; Middlesex County Massachusetts; migration of elements; mineralization; Mineralogy of non-silicates 01C; northeastern Massachusetts; orogeny; Paleozoic; plutonic rocks; pollutants; pollution; pyrite; sulfides; United States

A structural framework for the Nashoba Terrane in eastern Massachusetts. - Joseph P Kopera; Matthew A Massey (Abstracts with Programs - Geological Society of America, 2013)
The exhumation and tectonic significance of the migmatitic Cambro-Ordovician arc-complex of the Nashoba terrane, located between lower-grade rocks of the Avalon and Merrimack terranes in Massachusetts, has historically presented an enigma, in part, due to a lack of detailed analysis of internal structure. We propose a new terrane-scale structural model based on nearly a decade of detailed geologic mapping to provide a framework for future study. A subvertical NE-striking composite fabric (S (sub n/n-1) ) forms the dominant structural grain of the terrane. S (sub n) commonly deforms an older layer-parallel foliation (S (sub n-1) ) about meter- to kilometer-scale, upright to steeply inclined, NE- and SW-plunging, tight disharmonic folds (F (sub n) ). In the Nashoba Formation migmatites, S (sub n) commonly transposes a subhorizontal S (sub n-1) enveloping surface into spaced meter-scale subvertical shear bands that are absent in the dominantly metavolcanic Marlborough Formation. Fold axis-parallel mineral stretching and intersection lineations (L (sub n) ) are locally overprinted on S (sub n) by subhorizontal peak metamorphic to retrograde mineral lineations (L (sub n/n+1) ). Ambiguous D (sub n) kinematics in the NE transition SW along strike to top-to-NW normal fold vergence and drag along steep north-dipping S (sub n) axial planes and S (sub n) - S (sub n+1) shear bands. Later strain (S (sub n+1) - S (sub n+2) ) appears to be progressively partitioned at lower grade to pre-existing S (sub n) shear bands and discrete internal and terrane bounding fault zones which display early high-grade top-to-SE dextral or sinistral motion (S (sub n-1) - S (sub n) ) broadly overprinted by lower-grade top-NW movement (S (sub n+1) ). We propose a tentative tectonic history incorporating sparse existing geochronologic and petrologic studies: Top SW D (sub n-1) motion coeval with approximately 425 Ma sill-grade metamorphism and possible accretion. D (sub n) initiating syn approximately 395 Ma peak metamorphism with migmatite generation along S (sub n) and progressive bulk fabric development largely complete by the intrusion of the relatively undeformed approximately 349 Ma Indian Head Hill granite. Exhumation can be accommodated by well-documented syn-to-post D (sub n) regional sinistral motion combined with progressively lower grade top-NW extension along discrete structures continuing through deposition and deformation of presumed Carboniferous basin sediments along the terrane boundary.
Keywords: #StaffPubs; Cambrian; eastern Massachusetts; exhumation; fabric; fault zones; faults; foliation; massachusetts; metamorphism; Nashoba terrane; Ordovician; Paleozoic; Structural geology; tectonics; United States